Ramie type full-mixed pellet feed capable of preventing urolithiasis in mutton sheep and preparation method thereof - ZHAO NA; CHEN FANG; ZHANG NAIFENG; YAN NIANDONG; DIAO QIYU; YANG XUEHAI; GUO WANZHENG; WEI JINTAO (2016)
Ramie type full-mixed pellet feed capable of preventing urolithiasis in mutton sheep is prepared by mixing 20-50% of ramie and other crops and is characterized in that in the feed, there is 0.05-0.1% of Chinese herbal additives, the ramie, other crops and Chinese herbal additives add up to 100% by weight, and the Chinese herbal additives include, by weight: 30-40 parts of Rhizoma Atractylodis Macrocephalae, 9-12 parts of Semen Plantaginis, 0.1-1.0 part of vitamin A acetate and 47-60.9 parts of a support. The feed can effectively relieve urolithiasis with dysuria dominant due to severe imbalance of ramie calcium-phosphorus ratio, so that growth performance of mutton sheep is improved and the addition of ramie in mutton sheep daily ration is increased. 预防肉羊尿石病的苎麻型全混合颗粒饲料，它由20-50%的苎麻和其他农作物混合而成，其特征在于：饲料中有0.05-0.1%中草药添加剂，苎麻、其他农作物和中草药添加剂的重量总和为100%；所述的中草药添加剂的重量组分为：白术30-40份，车前子9-12份，维生素A乙酸酯0.1-1.0份，载体47-60.9份。能够有效的缓解由于苎麻钙磷比严重不平衡导致的以肉羊排尿困难为主要症状的尿石病，从而提高了肉羊的生长性能及苎麻在肉羊日粮中的添加量。